ETHICAL CODES IN EDUCATIONAL INSTITUTIONS OF UZBEKISTAN AS A TOOL TO COUNTER CORRUPTION IN THE NATIONAL EDUCATION SYSTEM - Mirzaev Rakhmatulla Ibadullayevich (Scholar Express Journals, 2022)
This article is devoted to the topical issue of improving the effectiveness of combating corruption in the education system of Uzbekistan. The article’s aim is to show the potential of the application of ethical codes in the education system as an effective means of combating corruption in all the educational institutions in Uzbekistan. The research methods were the following: analysis of scientific literature and legal acts, comparative legal analysis, induction, deduction and modeling. The article’s author comes to the conclusion that the scientific community has developed and applied many effective mechanisms for combating corruption in the education system, based on systems of monitoring, control, prevention, and the use of legal instruments. However, in the Republic of Uzbekistan there are no ethical codes for teachers in educational institutions, which are very effective in Western countries. The article’s author proposed an algorithm for the development and adoption of the ethical code of a teacher and making changes to it, which allows you to regulate in detail all aspects of the professional ethics of teachers
Keywords: Combating corruption; improving effectiveness; education system; ethical codes